2022
DOI: 10.3390/cells11152423
|View full text |Cite
|
Sign up to set email alerts
|

Excessive Oxalic Acid Secreted by Sparassis latifolia Inhibits the Growth of Mycelia during Its Saprophytic Process

Abstract: Sparassis latifolia is an edible and medicinal mushroom in Asia commercially cultivated on substrates containing pine sawdust. Its slow mycelial growth rate greatly increases the cultivation cycle. In this study, we mainly studied the role of oxalic acid (OA) secreted by S. latifolia in its saprophytic process. Our results show that crystals observed on the mycelial surface contained calcium oxalate monohydrate (COM) and calcium oxalate dihydrate (COD) according to X-ray diffraction (XRD). Vegetative mycelia s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…The degradation ability of lignocellulose was directly related to wood degradation by the mycelium, and will directly affect the growth rate [ 29 ]. Furthermore, our previous study also demonstrated that the activities of the lignocellulose-degrading enzyme of S. latifolia significantly reduced under high oxalic acid concentration [ 5 ]. Therefore, the low degradation efficiency of S. latifolia to lignocellulose under high oxalic acid concentration will inevitably reduce its growth rate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The degradation ability of lignocellulose was directly related to wood degradation by the mycelium, and will directly affect the growth rate [ 29 ]. Furthermore, our previous study also demonstrated that the activities of the lignocellulose-degrading enzyme of S. latifolia significantly reduced under high oxalic acid concentration [ 5 ]. Therefore, the low degradation efficiency of S. latifolia to lignocellulose under high oxalic acid concentration will inevitably reduce its growth rate.…”
Section: Discussionmentioning
confidence: 99%
“…For the pure culture of S. latifolia , a mycelial disc (diameter: 5 mm) was cultured on the center of potato dextrose peptone agar (PDPA) at 24 °C [ 15 ]. To grow mycelia, 10 mycelial discs (5 mm) of S. latifolia were inoculated into pine sawdust medium (PSM, 76% pine sawdust, 18% bran, 2% corn flour, 1.5% sucrose, 1.5% gypsum, and 1% calcium superphosphate) in a bag (17 × 35 cm) and incubated at 24 °C [ 5 ]. To identify the expression profiles of target genes affected by excessive oxalic acid, the mycelia were collected from PSM (CK), PSM with 10 mM oxalic acid (OA), and 4 mM 3,3-difluorooxaloacetate (IOA, an inhibitor of oxalic acid synthesis) after 20 days of incubation at 24 °C, mixed thoroughly, frozen immediately in liquid nitrogen, and stored at −80 °C for RNA extraction.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation